Developing biomarkers of TDP‐43‐related splicing dysfunction in frontotemporal dementia. (December 2021) - Seddighi, Sahba; Hill, Sarah; Brown, Anna‐Leigh; Qi, Andy; Hawrot, James; Coon, Steven; Petrucelli, Leonard; Fratta, Pietro; Ward, Michael
Abstract: Background: Frontotemporal dementia (FTD) is a rapidly progressive neurodegenerative disorder characterized by prominent atrophy of the frontal and temporal lobes and marked language and/or behavioral disturbances. Mislocalization of the TAR DNA‐binding protein 43 (TDP‐43) – characterized by both its nuclear loss and its cytosolic accumulation – occurs in up to 50% of FTD cases. Recent evidence from our group and others demonstrates that loss of TDP‐43‐dependent splicing activity occurs in FTD patient brains, is an early disease phenomenon, and contributes directly to neuronal death. Monitoring the products of TDP‐43 related mis‐splicing may, thus, yield promising biomarker candidates of early cellular dysfunction in FTD. Method: We propose a series of proteogenomic studies in human iPSC neurons, post‐mortem brain, and patient biospecimens to identify and develop protein‐based biomarkers of RNA mis‐splicing in FTD. First, we will identify pathologic RNA splicing changes and protein products of mis‐splicing that occur in the context of TDP‐43 depletion in iPSC‐derived neurons. We will next determine which of these predicted transcripts and de novo proteins occur in post‐mortem human FTD brains, as a crucial first step in biomarker development. Finally, we will develop CSF biomarkers of FTD‐related mis‐splicing through a combination of targeted proteomics and ELISA‐based assays of lead candidate biomarkers. Result: Using CRISPRi knockdown of TDP‐43 in i 3 Neurons followed by total RNAseq, we detected cryptic exon formation in STMN2 as well as hundreds of additional transcripts. We developed a proteogenomic informatic pipeline to detect de novo protein products of mis‐spliced transcripts in TDP‐43 deficient i3Neurons, revealing two in‐frame de novo peptides in the MYO18A transcript. Furthermore, we detected 38 of these mis‐spliced transcripts in ALS/FTD post‐mortem cortex, including MYO18A. Conclusion: These preliminary studies indicate that our i 3 Neuron CRISPRi pipeline can predict disease‐relevant markers of TDP‐43 mis‐splicing and suggest a proteogenomic workflow for development of novel protein‐based biomarkers of mis‐spliced transcripts.Together, these efforts will yield early biomarkers of TDP‐43 related cellular dysfunction that can act as surrogate measures of disease onset and progression in FTD.